Els castells de Corbera i de Cullera: de hisn musulmà a castrum cristià. - HIDALGO, PABLO CLARI (Scripta)
During the Islamic period and the first years after the conquest, the valencian's castles, were one of the most important elements regarding the vertebration of the valencian society. On the current academic paper, we are going to analyze the evolution of two valencian castles, even though both of them are close to each other. They become different versions, once the conquest became a reality. These are the castles of Corbera and Cullera. Both constructions have an Islamic origin and because of that their original function is similar, even thought, after the conquest everyone of them will live a different destiny, marked in this case, by their more or less strategic location.